Perilaku Konsumen Dalam Pembelian Jamur Tiram Segar Di Kabupaten Probolinggo - Lidyana, Novita (Universitas Panca Marga, 2023)
This research aims to determine the characteristics of oyster mushroom consumers in Semampir Market, Probolinggo Regency. This research was carried out at the Semampir Traditional Market by taking oyster mushroom consumer respondents. The research was carried out in August 2023. The analytical method used in this research refers to analytical techniques in reasoned action theory, namely the model developed by Fishbein. The results obtained from this research are that 92% of oyster mushroom consumers are female. Mushroom consumers are mostly distributed in the age group 35 – 44. Formal education is high school graduation. Consumer characteristics based on income can be seen that consumers who buy the most oyster mushrooms have an income ranging from 1.5 million - 3 million or as much as 50%. Consumer attitudes towards purchasing oyster mushrooms are positive with a score of 4.104, which overall shows the consumer's attitude. of oyster mushrooms in the Semampir Market, Probolinggo Regency is on a